2010
DOI: 10.1210/en.2009-1100
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Hepatic Lipase Are Lean and Protected against Diet-Induced Obesity and Hepatic Steatosis

Abstract: Hepatic lipase (HL)-mediated lipoprotein hydrolysis provides free fatty acids for energy, storage, and nutrient signaling and may play a role in energy homeostasis. Because HL-activity increases with increased visceral fat, we hypothesized that increased HL-activity favors weight gain and obesity and consequently, that HL deficiency would reduce body fat stores and protect against diet-induced obesity. To test this hypothesis, we compared wild-type mice (with endogenous HL) and mice genetically deficient in HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
5
30
2
2
Order By: Relevance
“…On the other hand, loss of intracellular TGH/Ces3-lipase which, by contrary, reduces blood lipids and improves glucose tolerance, ameliorated hepatic lipid deposition (Wei et al 2010). Surprisingly, a previous study reported decreased BW gain and reduced hepatic steatosis in HLdeficient mice (Chiu et al 2010). These seemingly discrepancy between these later results and the findings of the present study, might be related to the different dietary regimens used in both studies.…”
Section: Discussioncontrasting
confidence: 93%
“…On the other hand, loss of intracellular TGH/Ces3-lipase which, by contrary, reduces blood lipids and improves glucose tolerance, ameliorated hepatic lipid deposition (Wei et al 2010). Surprisingly, a previous study reported decreased BW gain and reduced hepatic steatosis in HLdeficient mice (Chiu et al 2010). These seemingly discrepancy between these later results and the findings of the present study, might be related to the different dietary regimens used in both studies.…”
Section: Discussioncontrasting
confidence: 93%
“…The increased energy expenditure we have observed in fat-fed WT mice measured by indirect calorimetry has been reported in other studies [43,44]. This increase was not observed in Prkce −/− mice after 1 week of fat feeding, which is in agreement with the increased hepatic lipid accumulation in these animals at this time.…”
Section: Discussionsupporting
confidence: 92%
“…46 The positive correlation of FTO and PGC1a expression seems to prove that FTO encodes a 2-oxoglutarate-dependent nucleic acid demethylase. 29 As STAT3 and HL are two key genes for glucose and fat metabolism, 47,48 their interaction with FTO overexpression suggests that FTO probably regulates food intake, glucose and fat metabolism through the STAT3 and HL pathways. FTO also increased the expression of GHSR, AMPKb, IGF1R, Leptin-R and PPARa, but these effects are less obvious and are not significant (P40.05).…”
Section: Discussionmentioning
confidence: 99%